PENGEMBANGAN MESIN PENETAS TELUR MENGGUNAKAN PEMERATAAN PANAS BUATAN - Eddi Indro Asmoro; Henggar Kresdianto (Jurnal Ilmiah Dinamika Teknik, 2021)
One of the mainstay businesses for farmers engaged in animal husbandry is raising chickens and ducks. Every year statistical data records that the community's need for chicken meat continues to increase. Indirectly this will have a positive impact on farmers, especially chicken farmers. Chicken farmers will try to increase the chicken breeding business, which aims to prevent the decline in broilers and laying hens. In this research, an automatic egg incubator has been made by implementing an artificial heating equalization method. The egg incubator is made to pay attention to the ideal temperature conditions for incubating chicken eggs, namely 35.3 0C - 40.5 0C, with humidity in the machine ranging from 60%-70%. This machine has a capacity for 100 eggs. This egg incubator is a modification of a previously made tool which is equipped with a fan as air circulation. And you don't need a roller to turn or turn the eggs because the eggs have gotten an even heat.